2004
DOI: 10.1152/ajpregu.00569.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role of the medullary lateral tegmental field in reflex-mediated sympathoexcitation in cats

Abstract: We tested the hypothesis that blockade of N-methyl-D-aspartate (NMDA) and non-NMDA receptors on medullary lateral tegmental field (LTF) neurons would reduce the sympathoexcitatory responses elicited by electrical stimulation of vagal, trigeminal, and sciatic afferents, posterior hypothalamus, and midbrain periaqueductal gray as well as by activation of arterial chemoreceptors with intravenous NaCN. Bilateral microinjection of a non-NMDA receptor antagonist into LTF of urethane-anesthetized cats significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
33
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 47 publications
9
33
0
Order By: Relevance
“…The inferior cardiac and vertebral branches of the left stellate ganglia were exposed retropleurally by removing the head of the 1st rib (31,46). These nerves project to the heart and vasculature of the forelimb, respectively.…”
Section: Sympathetic and Phrenic Nerve Recordingsmentioning
confidence: 99%
See 3 more Smart Citations
“…The inferior cardiac and vertebral branches of the left stellate ganglia were exposed retropleurally by removing the head of the 1st rib (31,46). These nerves project to the heart and vasculature of the forelimb, respectively.…”
Section: Sympathetic and Phrenic Nerve Recordingsmentioning
confidence: 99%
“…Several laboratories have shown that this region of the cat brain stem contains neurons with activity correlated to SND (7-9, 12, 18, 30, 56), and chemical activation of the LTF can alter blood pressure (17,26,32,41,54). Importantly, there is a growing body of evidence supporting the view that, at least in the cat, the LTF plays a crucial role not only in setting the basal level of SND (9, 10, 45) but also in mediating responses to activation of baroreceptor and chemoreceptor afferents (45,46). Specifically, blockade of non-N-methyl-D-aspartate (non-NMDA) receptors in the LTF reduced the level of basal SND and the sympathoexcitatory effect of arterial chemoreceptor activation (10,45,46), whereas blockade of NMDA receptors attenuated baroreflexmediated sympathoinhibition (45).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, blockade of N -methyl-D-aspartate (NMDA) receptors in the LTF abolished baroreceptor reflex control of sympathetic activity (Barman and Gebber 1987). In a recent study in cats, the same group showed that a blockade of non-NMDA receptors in the LTF significantly attenuated the reflex increase in cardiac and vertebral sympathetic nerve activity in response to electrical stimulation of vagal afferents or by activation of arterial chemo receptors (Orer et al 2004). On the other hand, the reflex sympathetic activation, in response to electrical stimulation of the sciatic or trigeminal nerve, was not affected by previous glutamatergic blockade within the LTF.…”
Section: The Rostral Ventrolateral Medulla and The Generation Of The mentioning
confidence: 96%